2005
DOI: 10.1016/j.livprodsci.2004.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of active immunization against GnRH on androstenone concentration, growth performance and carcass quality in intact male pigs

Abstract: Das Ziel dieser Studie war, die Wirkung der aktiven Immunisierung gegen das Gonadotropin Releasing Hormon (GnRH) bei männlichen Schweinen zu untersuchen und mit der chirurgischen Kastration zu vergleichen. Ferkel wurden randomisiert und in zwei Gruppen unterteilt: 263 Tiere für die chirurgische Kastration (SC) und 270 für die Immunokastration (IC). Der chirurgische Eingriff wurde in den ersten 14 Lebenstagen durchgeführt und die Impfung mit Improvac®, CSL, Australia, zweimal im Abstand von 4 bis 5 Wochen; die … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
72
1
16

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 22 publications
10
72
1
16
Order By: Relevance
“…In a field study of Jaros et al (2005), using 270 pigs immunised with Improvac R and 263 surgical castrates, the androstenone concentrations between both groups were not significantly different. Also no significant differences were registered for daily growth rate.…”
Section: Immunocastrationmentioning
confidence: 90%
See 1 more Smart Citation
“…In a field study of Jaros et al (2005), using 270 pigs immunised with Improvac R and 263 surgical castrates, the androstenone concentrations between both groups were not significantly different. Also no significant differences were registered for daily growth rate.…”
Section: Immunocastrationmentioning
confidence: 90%
“…Several experiments have been carried out in recent years in order to analyse the advantages of immunocastration by means of Improvac R (Dunshea et al, 2001;Zeng et al, 2002;Cronin et al, 2003;Jaros et al, 2005), or other vaccines ), compared to surgical castration. In all these tests, efficacy of the immunisation was over 97% of the treated pigs and, in most cases, immunised pigs were generally found to have a higher growth rate and better feed efficiency.…”
Section: Immunocastrationmentioning
confidence: 99%
“…Another explanation is that some animals do not react to the vaccination, or have not been correctly vaccinated. The so-called nonresponders have been identified by Zeng et al (2002a), Jaros et al (2005) and Hilbe et al (2006). …”
Section: Meat Qualitymentioning
confidence: 99%
“…Immunological blocking of the signal from GnRH decreases the production of LH and -E-mail: Kristina.Andersson@huv.slu.se testicular steroids. It has been demonstrated that vaccination against GnRH reduces the concentration of testicular steroids, including androstenone, along with the size of reproductive organs and sperm numbers (Bonneau et al, 1994;Jaros et al, 2005;Einarsson et al, 2009). Tuyttens (2002) reviewed the effects of castration on welfare of pigs and concluded that 'Evaluating the animal welfare implications of not castrating male piglets requires the delicate balancing of an abolishment of a short-term pain sensation, the preservation of the animal's integrity, and a potentially lower morbidity and mortality, on the one hand, against a likely increase in agonistic behaviour on the other'.…”
Section: Introductionmentioning
confidence: 99%